Sustainable development 20 years on from the Earth Summit : progress, gaps and strategic guidelines for Latin America and the Caribbean (UN New YorkUS, 2012)
Analyses the progress made and difficulties encountered in Latin America and the Caribbean in implementing global commitments on sustainable development since 1992. Proposes guidelines for moving towards sustainable development in the region.\n
Keywords: SUSTAINABLE DEVELOPMENT